CORRELATION BETWEEN SOCIAL SUPPORT AND SOCIAL WELL-BEING AMONG UNDERGRADUATES IN ENUGU STATE, NIGERIA - Aniagolu, Hyacinth (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Social well-being is an essential component of schoolwork engagement and educational achievement. However, contemporary society offers numerous conditions that interfere with the well-being of students. The present study examined the correlation between social support and the social well-being of undergraduates in Enugu state. Two hundred and fourteen students enrolled in three public tertiary institutions in Enugu State, Nigeria, participated in the study. They were randomly pooled from different departments in the selected institutions. The respondents completed a self-report measure of the Social Well-being Scale, the Multidimensional Scale of Perceived Social Support (MSPSS). The regression model showed that social support positively correlated with social well-being, F (1, 212) = 21.36, p < 0.05. Furthermore, the R2 indicated that the predictor variable contributed 16.4% of the variance in the social well-being of students in Enugu state. The finding provides valuable data for the promotion of the well-being of undergraduates.